Economia Criativa e a Mídia Radical: laboratórios experimentais para a inovação de plataformas midiáticas, conteúdos e recursos midiáticos - Xavier, Juarez Tadeu de Paula [UNESP] (My University, 2013)
The Creative Economy is an experimental laboratory for the creation , innovation , invention and reinvention of the universe of media - analog and digital . The scenery in the media and converging technologies favors the process of “ creative destruction and destructive creation “ of this field . The mapping of basins and technological corridors distributed through the territory of concentrated areas creates an infrastructural chassis for the production of content , information and entertainment . As locus and logos of immaterial production , digital ecology that gives speed to the flow of production - planning, fundraising , publishing , distribution and enjoyment - and allows the dispossession of their local clusters , the fragmentation and dilution of their creative chains . The collective cultural production and creation appropriating these capilarizados articles and produce content against political, economic and social status quo . The land is fertile and favorable to the emergence of radical media and rebels that recreate the public sphere , and edit poor public spheres , alternative , radical and efficient , the tactical point of view . This article aims to contribute to studies and research that scour the ecosystem of the media for understanding the management of their creative processes, actors and critics of tangible and intangible resources that support their communication actions .

A Economia Criativa é o laboratório experimental para a criação, inovação, invenção e reinvenção do universo das mídias analógicas e digitais. O cenário nas mídias e tecnologias convergentes favorece o processo de criação destrutiva e destruição criativa desse campo. A cartografia das bacias e corredores tecnológicos distribuídos pelo território das áreas concentradas cria um chassi infraestrutural para a produção de conteúdo, de informação e entretenimento. Como lócus e logos da produção imaterial, essa ecologia digital dá velocidade aos fluxos de produção planejamento, captação, edição, distribuição e fruição e permite a desterritorialização dos seus arranjos produtivos locais, com a fragmentação e pulverização das suas cadeias criativas. Os coletivos culturais de produção e criação se apropriam desses artefatos capilarizados, e produzem conteúdo contra o status quo político, econômico e social. O terreno é fértil e favorável ao surgimento de mídias radicais e rebeldes, que recriam a esfera pública, e editam esferas públicas precárias, alternativas, radicais e eficientes, do ponto de vista tático. Este artigo visa contribuir com os estudos e pesquisas que esquadrinham o ecossistema das mídias, para a compreensão da gestão dos seus processos criativos, dos seus atores críticos e dos recursos materiais e imateriais que dão suporte às suas ações comunicacionais.
Creative economy and radical media Experimental laboratories for innovation of media platforms, content and information resources
Keywords: Creative economy; Radical Media; Digital ecology; Deterritorialization; Operating chassis; Economia Criativa; Mídia radical; Ecologia digital; Desterritorialização; Chassi operacional